CHARACTERISTICS OF CHRONIC KIDNEY DISEASE PATIENTS WHOM USING CONTINUOUS AMBULATORY PERITONEAL DIALYSIS BASED ON SCORE PREDICTOR INADEQUACY DIALYSIS AND ITS REVIEW ACCORDING TO ISLAM VIEW - Nabiila Aurelia Abdullah; Linda Armelia; Muhammad Arsyad (Junior Medical Journal, 2022)
Chronic kidney disease (CKD) is a kidney disease that progressively loses of function and results in failure. Decreased kidney function can be characterized by glomerular filtration rate (GFR) 60 ml/min/1.73m2, creatinine and urea levels that increase simultaneously. This disease has various etiologies, one of the highest causes is a history of type 2 diabetes mellitus, obesity and hypertension. Therapy that is done to overcome this disease can be pharmacological therapy and kidney replacement therapy, one of the renal replacement therapies is dialysis which is further divided into two, namely hemodialysis and CAPD (Continuous Ambulatory Peritoneal Dialysis). CAPD users in Indonesia have not been widely used and the purpose of this study was to assess the characteristics of CKD patients using CAPD based on the predictor score of dialysis inadequacy. The research method uses Cross Sectional. The research sample was CKD CAPD patients in Bekasi who had met the inclusion criteria from January - March 2022. Data collection for research from medical record books and filling out google forms by respondents. There were 45 CKD patients using CAPD in Bekasi as respondents, the majority of whom were male 60%, the most age ranged from 20-60 years 93.3%, the most comorbid hypertension was 35.6%, and the majority had undergone CAPD therapy for 1-3 year 48.89%. In the results of the bivariate analysis of the relationship between the profile of CKD patients and the predictor score of dialysis inadequacy, which had a strong bond were GFR and serum creatinine levels.